Multitrophic biodiversity patterns and environmental descriptors of sub‐Arctic lakes in northern Europe - Lau, Danny C. P.; Christoffersen, Kirsten S.; Erkinaro, Jaakko; Hayden, Brian; Heino, Jani; Hellsten, Seppo; Holmgren, Kerstin; Kahilainen, Kimmo K.; Kahlert, Maria; Karjalainen, Satu Maaria; Karlsson, Jan; Forsström, Laura; et al. (Blackwell Scientific, 2022)
1. Arctic and sub-Arctic lakes in northern Europe are increasingly threatened by climate change, which can affect their biodiversity directly by shifting thermal and hydrological regimes, and indirectly by altering landscape processes and catchment vegetation. Most previous studies of northern lake biodiversity responses to environmental changes have focused on only a single organismal group. Investigations at whole-lake scales that integrate different habitats and trophic levels are currently rare, but highly necessary for future lake monitoring and management. 2. We analysed spatial biodiversity patterns of 74 sub-Arctic lakes in Norway, Sweden, Finland, and the Faroe Islands with monitoring data for at least three biological focal ecosystem components (FECs)—benthic diatoms, macrophytes, phytoplankton, littoral benthic macroinvertebrates, zooplankton, and fish—that covered both pelagic and benthic habitats and multiple trophic levels. 3. We calculated the richnessrelative (i.e. taxon richness of a FEC in the lake divided by the total richness of that FEC in all 74 lakes) and the biodiversity metrics (i.e. taxon richness, inverse Simpson index (diversity), and taxon evenness) of individual FECs using presence–absence and abundance data, respectively. We then investigated whether the FEC richnessrelative and biodiversity metrics were correlated with lake abiotic and geospatial variables. We hypothesised that (1) individual FECs would be more diverse in a warmer and wetter climate (e.g. at lower latitudes and/or elevations), and in hydrobasins with greater forest cover that could enhance the supply of terrestrial organic matter and nutrients that stimulated lake productivity; and (2) patterns in FEC responses would be coupled among trophic levels. 4. Results from redundancy analyses showed that the richnessrelative of phytoplankton, macrophytes, and fish decreased, but those of the intermediate trophic levels (i.e. macroinvertebrates and zooplankton) increased with decreasing latitude and/or elevation. Fish ...